Investment Analysis and Risk Prevention Mechanisms - Aktamov Bobirjon; Ochilov Bobur (Peerian Journals Publishing, 2023)
This article examines the essence of the attractiveness of the investment climate, the theory of international indices recognized by the world, which assesses the investment potential, the views of economists on increasing investment attractiveness in attracting foreign investment. At the same time, the methods of determining the investment flow of developed countries, the negative and positive factors affecting investment attractiveness are analyzed. In addition, the necessary mechanisms for attracting foreign investment and scientific conclusions and recommendations to increase investment attractiveness have been developed
Keywords: investment attractiveness; investment potential; investment policy